Effects of dry-extruded whole soybeans on growth performance of nursery pigs and growth performance, carcass characteristics, and stomach morphology of finishing pigs - I H Kim; Robert H Hines; L L Burnham; Terry L Gugle; Joe D Hancock (Kansas Agricultural Experiment Station Research Reports, 1995)
In a 3 I-d nursery experiment, replacing soybean meal (SBM) with dry-extruded whole soybeans (DEWS) tended to improve F/G (6% overall difference), but ADG was not affected. Adjusting the diet with DEWS to the nutrient:calorie ratio of the diet with SBM did not greatly improve growth performance compared to the diet that was simply formulated to the same concentration of lysine as the diet with SBM. In a second experiment (with finishing pigs), 50 and 100% of the SBM in a corn-based diet was replaced with DEWS. Replacement resulted in 2% greater ADG and 8% better F/G, without significantly increasing carcass fatness or the incidence of stomach ulcers. Our data suggest that DEWS are an acceptable (if not superior) alternative to SBM in diets for nursery and finishing pigs.; Swine Day, Manhattan, KS, November 16, 1995
Keywords: Swine day; 1995; Kansas Agricultural Experiment Station contribution; no. 96-140-S; Report of progress (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service); 746; Swine; Soybeans; Extrusion; Ulcers; Backfat